Structure elucidation of a thermostable organic solvent-tolerant recombinant HZ lipase and determination of its thermostability - Masomian, Malihe (2013)
The principles of enzyme activity and stability have become a growing interest for researchers in exploring how enzymes adapt in the presence of organic solvent and high temperatures. The structural studies and X-ray crystallography of enzymes could provide clues towards understanding of their properties and function. The atomic details of molecular structures could offer accurate models of molecular interactions that promote protein engineering to improve the application of protein. To realize the goal, thermostable and organic solvent tolerant HZ lipase from newly isolated local Aneurinibacillus thermoaerophilus strain HZ was crystallized to elucidate the molecular structure of the enzyme. Owing to the unique properties of HZ lipase, to study the functional genomics of this potentially important bacterium requires not only overexpressing the corresponding genes but also detailing understanding of molecular protein structure. HZ lipase gene was isolated and cloned into plasmid pET32b and expressed into E. coli BL21 (DE3). The optimum lipase expression was obtained after 8 h incubation at 30 °C post induction with 0.025 mM IPTG, where the lipase act ivity was approximately 145 times higher than wild type HZ lipase. The presence of His tag was confirmed by western blot analysis. To purify the enzyme,affinity chromatography was used as the first step following the treatment of the fusion protein at 20 °C to get mature HZ lipase without using any protease treatment step. A high purification yield of 78.9% with 1.3-fold purification and 21.8 mg total purified protein was obtained from 50 mL culture. The mature lipase was highly active at 65 °C and pH 7 with a half-life of 45 min at 60 °C and 2 h 15 min at 55 °C. HZ lipase showed an enhancement effect in the presence of Li+, Na+, K+, Rb+, Cs+, Mg2+, Ca2+,Sr2+ and Mn2+ after 30 min treatment. HZ lipase activity was increased by glycerol and dimethyl sulfoxide, very polar organic solvents, however its activity was inhibited in the presence of alcohols. A structural model of the HZ lipase was built using YASARA structure (Yet Another Scientific Artificial Reality Application) from a known three-dimensional structure (T1 lipase, PDB ID: 2DSN) which it had the highest sequence identity (57%) with the HZ lipase. The predicted 3D structure of HZ lipase revealed the topological organization of α/β-hydrolase fold consisting of 10 α-helices and 13 β-strands. Ser113, His308 and Asp350 were assigned as catalytic triad residues. In order to get a more accurate structure, HZ mature lipase was successfully crystallized via vapordiffusion and counter diffusion techniques. However, the crystal formed had poor quality to diffract X-ray in a house X8 Proteum, BRUKER. Therefore, crystallization was performed under microgravity conditions in space as well as in a ground control. The ground control crystal had poor quality for diffraction of synchrotron X-rays. However, the microgravity HZ lipase crystal diffracted to 1.58 Å resolution and belonged to the primitive monoclinic space group P1 21 1. The phase problem was solved by the Balbes method and T1 lipase crystal structure (PDB entry: 2DSN) was used as the search model. Based on Balbes calculation, the crystal contained eight molecules per asymmetric unit, with a Matthews’s coefficient of 2.14 Å Da-1 and solvent content of 42.60%. The generated model was further built and refined up to 1.8 Å with final R factor and R free of 0.2905 and 0.3579, respectively. The crystal structure of HZ lipase showed the presence of two metal ions, Zn2+ and Ca2+. The effect of stabilization factors on HZ lipase thermostability was studied through a rational design strategy. The critical point residues were identified in order to increase the number of ion pairs in HZ lipase structure. The substitutions of Trp225 with Lys and Val361 with Arg were done using YASARA software and the new 3D structure was designated as mutant lipases (W225K and V361R lipases). The analysis of mutated lipases showed one and two new additional ion pairs in W225K and V361R lipases, respectively. Meanwhile, both mutants showed reduction in the solvent accessible surface area calculated by the YASARA software.The HZ lipase mutants W225K and V361R were constructed by site-directed mutagenesis. Mutant V361R lipase showed a decrease in optimum activity temperature from 65 to 55 °C,but the pH stability profile of the mutant was improved compared to the HZ lipase. Mutant W225K lipase showed a half-life of 3 h 45 min at 55 °C and 1 h 20 min at 60 °C, which was higher than HZ lipase thermostability. Superposition analysis of V361R with HZ lipase showed that α-helices became shorter. Hence, the α-helix stabilization is important for HZ lipase stability. However, both computational and experimental analysis of W225K lipase indicated that presence of additional ion paircould increase the stability of enzyme. In addition, the activity of HZ lipase strictly depends on the length and hydrophobicity of its lid. In conclusion, crystallization analysis of HZ lipase indicated that the crystals grown under microgravity are superior to the control crystals grown on earth under normal gravity. The structural elucidation of HZ lipase revealed exclusive features that made this enzyme unique in structure and valuable in fundamental study. In addition, overall analysis showed that HZ lipase stability depends on multiple factors and its lid play important roles in lipase activity.